2021
DOI: 10.1002/pssa.202100536
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Activity Enhancement of Anatase/Rutile‐Mixed Phase TiO2 Nanoparticles Annealed with Low‐Temperature O2 Plasma

Abstract: Photodecomposition and photobactericidal activities of anatase/rutile-mixed phase TiO 2 nanoparticles annealed with low-temperature O 2 plasma are clarified by comparing them with those annealed in ambient air. The photocatalytic activities of plasma-assisted-annealed sample greatly enhance as compared with the untreated sample, under not only UV irradiation but also visible-light irradiation. The photocatalytic activities of air-annealed samples do not enhance under UV irradiation but enhance under visible-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 71 publications
0
0
0
Order By: Relevance
“…Similarly, Hojo et al [105] also successfully introduced oxygen defects in a TiO 2 :Nb film by annealing the sample with Ar plasma irradiation. Recently, Kawakami et al [106] reported a kind of anatase/rutile mixed phase TiO 2 nanoparticle with many oxygen deficiencies, which were obtained by annealing the sample with low-temperature O 2 plasma. There are also excited species, such as ozone and OH generated during the plasma discharge in water.…”
Section: Plasma-assisted Depositionmentioning
confidence: 99%
“…Similarly, Hojo et al [105] also successfully introduced oxygen defects in a TiO 2 :Nb film by annealing the sample with Ar plasma irradiation. Recently, Kawakami et al [106] reported a kind of anatase/rutile mixed phase TiO 2 nanoparticle with many oxygen deficiencies, which were obtained by annealing the sample with low-temperature O 2 plasma. There are also excited species, such as ozone and OH generated during the plasma discharge in water.…”
Section: Plasma-assisted Depositionmentioning
confidence: 99%